2015
DOI: 10.3892/or.2015.3923
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba extract enhances chemotherapy sensitivity and reverses chemoresistance through suppression of the KSR1-mediated ERK1/2 pathway in gastric cancer cells

Abstract: Kinase suppressor of Ras 1 (KSR1) is a scaffold protein that modulates the activation of the oncogenic mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) signaling pathway. Ginkgo biloba extract (EGb) 761 has been demonstrated to possess antitumor activity that may be related to the KSR1-mediated ERK signaling pathway. However, the roles and its underlying mechanism in gastric cancer are unclear. In the present study, 62 gastric cancer and matched normal tissues were exploited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 31 publications
(42 reference statements)
3
21
0
Order By: Relevance
“…A study observed that compared to the expression in the matched normal tissues, ERK1/2, p-ERK1/2, KSR1, and p-KSR1 were distinctly overexpressed in gastric cancer tissues, in association with TNM stage and the lymph metastasis [14] . Besides, the expressions of ERK1/2, p-ERK1/2, KSR1, and p-KSR1 are significantly related with each other, indicating that KSR1 might play a role in the oncogenesis and progression of gastric neoplasms [15] . Additionally, the KSR1-mediated ERK1/2 signaling pathway is inferred to be somehow associated with anticancer drug sensitivity and chemoresistance in GI tumors [13,15] .…”
Section: Other Scaffold Proteins In the Mapk Signaling Pathwaymentioning
confidence: 99%
See 3 more Smart Citations
“…A study observed that compared to the expression in the matched normal tissues, ERK1/2, p-ERK1/2, KSR1, and p-KSR1 were distinctly overexpressed in gastric cancer tissues, in association with TNM stage and the lymph metastasis [14] . Besides, the expressions of ERK1/2, p-ERK1/2, KSR1, and p-KSR1 are significantly related with each other, indicating that KSR1 might play a role in the oncogenesis and progression of gastric neoplasms [15] . Additionally, the KSR1-mediated ERK1/2 signaling pathway is inferred to be somehow associated with anticancer drug sensitivity and chemoresistance in GI tumors [13,15] .…”
Section: Other Scaffold Proteins In the Mapk Signaling Pathwaymentioning
confidence: 99%
“…Besides, the expressions of ERK1/2, p-ERK1/2, KSR1, and p-KSR1 are significantly related with each other, indicating that KSR1 might play a role in the oncogenesis and progression of gastric neoplasms [15] . Additionally, the KSR1-mediated ERK1/2 signaling pathway is inferred to be somehow associated with anticancer drug sensitivity and chemoresistance in GI tumors [13,15] .…”
Section: Other Scaffold Proteins In the Mapk Signaling Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…The leaf extract of ginkgo has been employed for treating cerebrovascular and cardiovascular diseases for centuries [2]. Modern pharmacological studies showed that G. biloba extract could be also used for the treatment of chronic schizophrenia and Alzheimer's disease, as well as possessing antitumor activity [3][4][5]. Terpene trilactones, which include ginkgolides and bilobalide, are surmised to be responsible for most of the pharmacological properties of G. biloba extracts.…”
mentioning
confidence: 99%